2014
DOI: 10.1007/s40299-014-0197-y
|View full text |Cite
|
Sign up to set email alerts
|

Does Touch-based Interaction in Learning with Interactive Images Improve Students’ Learning?

Abstract: This study aims to examine the effects of a touchscreen device (iPad in this study) on students' learning compared to a desktop PC in terms of tactile vision. The participants were 56 undergraduate students: 24 studied using a desktop PC (mouse-based interaction) and the others studied using a touchscreen device (touch-based interaction) about the human heart through interactive images. MANOVA results revealed a significant main effect for the device type. Three follow-up ANOVAs revealed that the students in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In this regard, research in the realm of multimodal learning analysis has assessed how students communicate, collaborate, and solve problems within a smart classroom [37]-an area of research recently stimulated by the evaluation of neuro-physiological data from these technology-based learning environments [42]. Indeed, it has been shown that users' tactile manipulation of tangible interfaces enables the development of cognitive and physical connections [35]-a research outcome supported by the higher students' ability to identify objects' parts and position when using touch-based smart-pad interfaces w. r. t. traditional mouse-based technology [20]. In this regard, to evaluate how digital classrooms might encourage students' learning, multimodal learning analyticsan emerging field of research that combines the study of different natural communication modalities, such as speech, writing, or gesturing-has been successfully taken into account [27,29].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, research in the realm of multimodal learning analysis has assessed how students communicate, collaborate, and solve problems within a smart classroom [37]-an area of research recently stimulated by the evaluation of neuro-physiological data from these technology-based learning environments [42]. Indeed, it has been shown that users' tactile manipulation of tangible interfaces enables the development of cognitive and physical connections [35]-a research outcome supported by the higher students' ability to identify objects' parts and position when using touch-based smart-pad interfaces w. r. t. traditional mouse-based technology [20]. In this regard, to evaluate how digital classrooms might encourage students' learning, multimodal learning analyticsan emerging field of research that combines the study of different natural communication modalities, such as speech, writing, or gesturing-has been successfully taken into account [27,29].…”
Section: Introductionmentioning
confidence: 99%